ADAMDEC1 and FGF2/FGFR1 signaling constitute a positive feedback loop to maintain GBM cancer stem cells - Jimenez-Pascual, Ana; Lathia, Justin D.; Siebzehnrubl, Florian A. (Molecular & cellular oncology, 2020)
Identification of targetable mechanisms that maintain glioblastoma cancer stem cells (CSCs) remain a priority. Our study reveals a new mechanism by which a disintegrin and metalloproteinase domain-like protein decysin 1 promotes CSC maintenance through the activation of a fibroblast growth factor autocrine signaling loop, which can be blocked pharmacologically.